Protection of Privacy Rights in The Digital Era Between Cybersecurity and Freedom of Information - Kaaisar Romolus Deo Sianipar; Rahmayanti Rahmayanti; Andi Gultom (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
The digital era has brought significant changes in the way humans access, store, and share information. Amidst these technological advances, major challenges have emerged to the protection of individual privacy rights. Personal information is increasingly easy to collect and process by various parties, both by state institutions, technology companies, and individual users. On the other hand, the need for freedom of information is also increasing, especially in the context of transparency, public participation, and data openness. The balance between cybersecurity and freedom of information is a crucial issue that must be addressed comprehensively. This paper aims to examine the protection of privacy rights in the digital era by highlighting the tension between data security efforts and demands for information openness. The method used is a literature study with a qualitative approach. The results of the study show that privacy protection requires clear regulations, such as the Personal Data Protection Law in Indonesia, as well as public awareness in protecting personal data. On the other hand, freedom of information must still be maintained so that it is not misused to violate individual rights. Therefore, a balanced approach is needed between regulation, education, and technology to create a digital space that is safe, fair, and respects human rights.